2022
DOI: 10.1111/ceo.14027
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis of glaucoma: Extracellular matrix dysfunction in the trabecular meshwork‐A review

Abstract: The trabecular meshwork regulates aqueous humour outflow from the anterior chamber of the eye. It does this by establishing a tunable outflow resistance, defined by the interplay between cells and their extracellular matrix (ECM) milieu, and the molecular interactions between ECM proteins. During normal tissue homeostasis, the ECM is remodelled and trabecular cell behaviour is modified, permitting increased aqueous fluid outflow to maintain intraocular pressure (IOP) within a relatively narrow physiological pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
32
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 230 publications
(295 reference statements)
0
32
0
2
Order By: Relevance
“…A major risk factor of glaucoma is elevated intraocular pressure (IOP), which is caused by dysfunction in the trabecular meshwork (TM) aqueous humor drainage pathway (Stamer and Acott, 2012). The extracellular matrix (ECM) of TM tissue is a source of outflow resistance and glaucomatous ECM differs in amount, structure and organization compared to normal TM tissue (Fuchshofer and Tamm, 2009;Tektas and Lutjen-Drecoll, 2009;Vranka et al, 2015;Acott et al, 2021;Keller and Peters, 2022). Glaucomatous TM tissue has altered biomechanics compared to age-matched tissue derived from non-glaucomatous TM tissue (Last et al, 2011;Raghunathan et al, 2018) Notably, glaucoma TM cells in culture display molecular memory and synthesize and assemble dysfunctional matrices similar to those found in situ (Raghunathan et al, 2018;Acott et al, 2021;Wirtz et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…A major risk factor of glaucoma is elevated intraocular pressure (IOP), which is caused by dysfunction in the trabecular meshwork (TM) aqueous humor drainage pathway (Stamer and Acott, 2012). The extracellular matrix (ECM) of TM tissue is a source of outflow resistance and glaucomatous ECM differs in amount, structure and organization compared to normal TM tissue (Fuchshofer and Tamm, 2009;Tektas and Lutjen-Drecoll, 2009;Vranka et al, 2015;Acott et al, 2021;Keller and Peters, 2022). Glaucomatous TM tissue has altered biomechanics compared to age-matched tissue derived from non-glaucomatous TM tissue (Last et al, 2011;Raghunathan et al, 2018) Notably, glaucoma TM cells in culture display molecular memory and synthesize and assemble dysfunctional matrices similar to those found in situ (Raghunathan et al, 2018;Acott et al, 2021;Wirtz et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…When they elevated the pressure to 17.6 mmHg, the elastic modulus of the TM in the LF region is 30.33 kPa while in the HF region is 2.72 kPa [ 58 , 134 ]. Keller similarly showed that the HF regions have a lower elastic modulus and are more compliant than the LF regions [ 135 ]. Our results are in very good agreement with Vranka and Keller, as we found larger short- and long-time shear moduli for the LF regions compared to the HF regions ( Table 3 and Table 4 ), so the HF regions are more compliant and dynamic in their homeostatic response to elevated pressure.…”
Section: Discussionmentioning
confidence: 99%
“…We found that a variety of genes associated with ECM and focal adhesion were downregulated in the TIPARP -overexpressing HTM cells by RNA-seq. Previous studies have demonstrated that the trabecular meshwork regulates aqueous humor outflow resistance by cells and their ECM interplay and ECM protein interactions 5 , 6 . Abnormal changes in the ECM have dramatic effects on trabecular meshwork function 22 , 23 .…”
Section: Discussionmentioning
confidence: 99%
“…IOP is determined by the balance between aqueous humor secretion and drainage mainly through the conventional outflow pathway consisting of the trabecular meshwork, juxtacanalicular tissue and Schlemm's canal 2,3 . Abnormally high resistance to aqueous humor outflow induced by trabecular meshwork malfunction is an important aetiology of POAG [4][5][6] . However, the underlying molecular and cellular mechanisms of increased resistance to aqueous humor outflow still need to be explored.…”
mentioning
confidence: 99%